2018
DOI: 10.1053/j.gastro.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

JTC801 Induces pH-dependent Death Specifically in Cancer Cells and Slows Growth of Tumors in Mice

Abstract: In a screen of agents that interact with GPCR pathways, we found JTC801 to induce pH-dependent cell death (alkaliptosis) specifically in cancer cells such as PDAC cells, by reducing expression of CA9. Levels of CA9 are increased in human cancer tissues. JTC801 might be developed for treatment of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 18 publications
(17 reference statements)
1
128
0
Order By: Relevance
“…cDNA from various cell samples was amplified using real-time quantitative PCR with specific primers (Table S2). The data were normalized to 18S RNA and the fold change was calculated via the 2 −ΔΔCt method (Song et al, 2018; Zhu et al, 2017). Relative concentrations of mRNA were expressed in arbitrary units based on the untreated group, which was assigned a value of 1.…”
Section: Star Methodsmentioning
confidence: 99%
“…cDNA from various cell samples was amplified using real-time quantitative PCR with specific primers (Table S2). The data were normalized to 18S RNA and the fold change was calculated via the 2 −ΔΔCt method (Song et al, 2018; Zhu et al, 2017). Relative concentrations of mRNA were expressed in arbitrary units based on the untreated group, which was assigned a value of 1.…”
Section: Star Methodsmentioning
confidence: 99%
“…Furthermore, JTC-801 demonstrated its anticancer effect in the ovarian cancer SKOV3 cell line, particularly on cell growth and metastasis (16). Song et al (12) reported that JTC-801 may be used for the treatment of pancreatic cancer. Similarly, the present study revealed the inhibitory effect of the drug on Hep G2 hepatoblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ORL1 may antagonize lipopolysaccharide-stimulated proliferation, migration and inflammatory signalling in human glioblastoma U87 cells (11). In a screening of agents that interact with GPCR pathways, Song et al (12) revealed that JTC-801 induces pH-dependent cell death (alkaliptosis) specifically in cancer cells, including pancreatic ductal adenocarcinoma cells, by reducing the expression of carbohydrate antigen 9, which is increased in human cancer tissues. JTC-801 may be used in the development of treatment for pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Alkaliptosis is a unique pHdependent form of RCD driven by intracellular alkalinization [27]. Song et al showed that JTC801 can induce a pHdependent cell death in human pancreatic cancer cells by activating NF-κB [28]. is form was found to be distinct from ferroptosis, necroptosis, and autophagy, and was defined as alkaliptosis.…”
Section: Nrf2/ho-1 Signaling Axis In Alkaliptosismentioning
confidence: 99%
“…Although NF-κB inhibitors can inhibit alkaliptosis [29], no effect of Nrf2 knockout alters JTC801-induced cell death [28]. However, as pathological significance of alkaloptosis and its core effector molecules are still being studied, the specific relationship is not yet clear.…”
Section: Nrf2/ho-1 Signaling Axis In Alkaliptosismentioning
confidence: 99%